PENGETAHUAN PETERNAK TENTANG ESTRUS PADA SAPI ACEH DENGAN TERJADINYA REPEAT BREEDING DI KABUPATEN PIDIE - Djoko Subagyo, Tongku N Siregar, Teuku Reza Ferasyi Dasrul, Mustafa Sabri (Jurnal Agroristek, 2020)
The study was aimed to determine the level of knowledge of farmers about cattle estrus Aceh with the occurrence of repeat breeding in Pidie District. Samples were obtained from secondary data reports for   animal husbandry Department  aceh Pidie 161 female cows study was. Carried out in the form of observational study with cross sectional approach. Primary data were collected by direct observation and interviews with questionnaires to farmers and inseminator. The data were analyzed descriptively. Chi Square test (X2) was used to determine the association between factors that cause, while Odds Ratio (OR) was used to calculate the strength of the association. The results of this study which has gained significantly associated (P less-than 0.05) on the incidence of repeat breeding is knowledge estrus  with  OR = 2.3. And the conclusion is. knowledge estrus against Aceh cattle repeat breeding associated with the occurrence of repeat positive or are associated.  Keywords:  knowledge estrus, repeat breeding, cattle Aceh